2010
DOI: 10.1161/strokeaha.110.583542
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cerebral Sinovenous Thrombosis From Symptom to Outcome

Abstract: Background and Purpose— Cerebral sinovenous thrombosis is a rare disease with severe neurological sequelae. The aim of this retrospective multicenter study was to investigate the clinical course, possible risk factors, and outcome of a cohort of neonatal patients with sinovenous thrombosis and, second, to estimate the incidence in The Netherlands. Methods— From January 1999 to March 2009, a review of all neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
140
3
38

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(197 citation statements)
references
References 34 publications
(49 reference statements)
16
140
3
38
Order By: Relevance
“…The lesions Reported outcomes after neonatal CSVT include death in 7% to 19% and neurologic impairments in 36% to 79% of survivors. 383,384,386 Adverse neurologic outcomes include cognitive and motor defi cits and in 20% to 40%, epilepsy. 387 The presence of infarcts at diagnosis and perinatal complications predict worse outcome.…”
Section: Neonates With Purpura Fulminansmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesions Reported outcomes after neonatal CSVT include death in 7% to 19% and neurologic impairments in 36% to 79% of survivors. 383,384,386 Adverse neurologic outcomes include cognitive and motor defi cits and in 20% to 40%, epilepsy. 387 The presence of infarcts at diagnosis and perinatal complications predict worse outcome.…”
Section: Neonates With Purpura Fulminansmentioning
confidence: 99%
“…393 The most common anticoagulant used is LMWH. 386,392,394 LMWH has been reported to be safe even in the presence of signifi cant thalamic hemorrhage. 395 The optimal dose and duration of anticoagulant treatment is not known.…”
Section: Neonates With Purpura Fulminansmentioning
confidence: 99%
“…In a multicenter, retrospective review by Berfelo et al, 2 (5%) of 41 neonates tested had FVL and 2 (11%) of 18 neonates tested had PTM. 20 In a retrospective nationwide population-based study, 10 infants ,1 year of age, including 7 neonates, were diagnosed with CVT. Inherited thrombophilia was present in only 1 (13%) of the 8 patients tested.…”
Section: Venous Thrombosis and Thrombophilia In Neonatesmentioning
confidence: 99%
“…CVST formed only less than 1 percentage in the present study as against the reported 5-13% of occurrence as a chance finding in cranial ultrasound. 25,26 We suggest performing MRA and MRV along with standard sequences in evaluation of neonatal seizures in order to detect vascular etiology.…”
Section: Discussionmentioning
confidence: 99%